1999
DOI: 10.1093/bja/82.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane requirements for tracheal intubation with and without fentanyl

Abstract: We studied 80 healthy ASA 1 patients (aged 20-52 yr) to determine if fentanyl affects sevoflurane requirements for achieving 50% probability of no movement in response to laryngoscopy and tracheal intubation (MAC-TI). Patients were allocated randomly to one of four fentanyl dose groups (0, 1, 2 and 4 micrograms kg-1). Patients in each group received sevoflurane at a pre-selected end-tidal concentration according to an 'up-down' technique. After steady state sevoflurane concentration had been maintained for at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 15 publications
3
56
2
4
Order By: Relevance
“…1,6 Because opioids decrease sevoflurane minimum alveolar concentration (MAC) and heart rate, they may reduce hemodynamic changes and time to tracheal intubation. [7][8][9][10] However asystole or severe hypotension may occur, probably because of inappropriate opioid dosing, and the effects of sevoflurane-alfentanil on the ease and speed of tracheal intubation have not been evaluated. 9,[11][12][13] Our study aimed to determine the dose of alfentanil required to decrease the time to tracheal intubation and blunt the increase in heart rate associated with an inhalation induction.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
See 1 more Smart Citation
“…1,6 Because opioids decrease sevoflurane minimum alveolar concentration (MAC) and heart rate, they may reduce hemodynamic changes and time to tracheal intubation. [7][8][9][10] However asystole or severe hypotension may occur, probably because of inappropriate opioid dosing, and the effects of sevoflurane-alfentanil on the ease and speed of tracheal intubation have not been evaluated. 9,[11][12][13] Our study aimed to determine the dose of alfentanil required to decrease the time to tracheal intubation and blunt the increase in heart rate associated with an inhalation induction.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…9 While maintaining a steady state concentration of sevoflurane, the MAC for tracheal intubation is reduced by 42% when adding 1 µg·kg -1 fentanyl. 8 The maintenance of a steady state concentration of sevoflurane used in these previous studies is relevant only for maintenance of anesthesia but not for induction. In the present study, we chose a different approach, maintaining alfentanil at steady state concentrations.…”
Section: Scores Group 0 Group25 Group 50 Group 75mentioning
confidence: 99%
“…The MAC-sparing effect of both fentanyl 12 and midazolam 13,14 can probably explain these results. Still, authors who have studied the administration of opioids or midazolam alone prior to IIAS have found conflicting results.…”
Section: Discussionmentioning
confidence: 90%
“…Still, authors who have studied the administration of opioids or midazolam alone prior to IIAS have found conflicting results. Some showed increased [7][8][9][10][11][12][13][14][15] time to loss of consciousness or time needed before laryngeal mask insertion, while others showed a decrease. [5][6][7][8][9][10] The choice of drugs and doses in this study was influenced by Muzi et al 10 who showed that this particular combination accelerated and improved conditions for endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl also has anti tussive action. Katohet al 22 suggested that fentanyl blocks afferent nerve impulses arising from stimulation of the pharynx, larynx and lungs during intubation.…”
Section: Discussionmentioning
confidence: 99%